2012
DOI: 10.1021/pr200965c
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Ripening Tomato Fruit Infected by Botrytis cinerea

Abstract: Botrytis cinerea, a model necrotrophic fungal pathogen that causes gray mold as it infects different organs on more than 200 plant species, is a significant contributor to postharvest rot in fresh fruit and vegetables, including tomatoes. By describing host and pathogen proteomes simultaneously in infected tissues, the plant proteins that provide resistance and allow susceptibility and the pathogen proteins that promote colonization and facilitate quiescence can be identified. This study characterizes fruit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 77 publications
(133 reference statements)
1
58
1
2
Order By: Relevance
“…Proteomics of tomato fruits infected by B. cinerea revealed changes in 186 proteins in mature green wild-type fruit, which were unaltered in red ripe (RR) wild-type and ripening inhibited ( rin ) mutant. However, fewer defense-related proteins were changed in mature green wild-type fruit than in RR and rin fruits (Shah et al, 2012). …”
Section: Proteomicsmentioning
confidence: 99%
“…Proteomics of tomato fruits infected by B. cinerea revealed changes in 186 proteins in mature green wild-type fruit, which were unaltered in red ripe (RR) wild-type and ripening inhibited ( rin ) mutant. However, fewer defense-related proteins were changed in mature green wild-type fruit than in RR and rin fruits (Shah et al, 2012). …”
Section: Proteomicsmentioning
confidence: 99%
“…Proteomic analysis of three types of tomato fruit infected by B. cinerea revealed that 186 tomato proteins were identified in common among red ripe and red ripe-equivalent ripening inhibited (rin) mutant tomato fruit infected by B. cinerea . However, the limited infections by B. cinerea of mature green wild type fruit resulted in 25 and 33% fewer defense-related tomato proteins than in red and rin fruit, respectively (Shah et al, 2012). …”
Section: Interaction Between Fruits and Fungimentioning
confidence: 99%
“…A β-1,3-glucanase gene (e.g., TomQ ' a ) is induced 1 day post-inoculation when unripe fruit is infected but no induction occurs in infections of ripe fruit, or as consequence of ripening (Cantu et al 2009 ). Later in infections (3 days post-inoculation), enhanced expression and accumulation of PR-proteins, such as the putative thaumatin-like protein SlPRP -23 , the possible chitinase, SlChi -like1 , and the β-1,3-glucanases, TomQ ' b and TomB13GLUB , was detected in both unripe and ripe fruit (Cantu et al 2009 ;Shah et al 2012 ). PR-proteins in fruit may not be effective in controlling B. cinerea infections since the Cnr mutation induces PR gene expression in fruit but the fruit are hyper-susceptible to B. cinerea .…”
Section: Pathogenesis-related Proteinsmentioning
confidence: 99%